Identificação de recursos florestais em três comunidades de agricultores familiares na estrada da várzea, no município de Silves-Am - Silva, Keuris Kelly Souza da (Instituto Nacional de Pesquisas da Amazônia - INPA, 2005)
This study was carried out in three communities at Road of Varzea at Silves municipality, Amazonas State, Brazil. The purpose was to establish features for use and management of wood and non-wood resources for the families of farmers that live at these communities. To establish these social, economic and environmental characteristics were made interviews with 34 families. It was verified that 73% of these families are from Amazonas but only 29% of them have a historic as farmer workers. These people`s biggest yearning is the improvement of local infrastructure, as the asphalt covering of the road, and better education conditions. The biggest obstacles to the execution of a communitarian forest handling or multiple use project is the fragility of social organization and an irregular land tenure situation. A forest inventory to determinate the wood economic potential it was made in a natural forest area at Silves municipality, Amazonas State, with nearly 3000 ha, surrounded by the access road to Silves, the Sanabani river and the Igarape-Acu. It was verified the prevalence of the following families - Lecythidaceae (430 specimens), Burseraceae (288 specimens), Lauraceae (247 specimens), Sapotaceae (246 specimens), Olacaceae (114 specimens) and Leguminoseae-Caesalpinoideae (102 specimens). These six families represented about 55% of all species included in the inventory. The most abundant species were Eschweilera odora (Poepp.) Miers., followed by Minquartia guianensis Aubr. And Protium apiculatum. For Importance Value Index and Cover Value Index there was also a prevalence of Eschweilera odora (Poepp.) Miers as dominant specie. The potential and the use of forest resources was studied through the application of 14 inventory etnobothanic at the three communities that revealed 26 bothanic families with economic potential. Nine main uses were elected - human feeding, animal feeding, as medicine, construction, cosmetic, fertilizer, domestic utensil/hunt and others. The bothanic families that presented a major cultural importance were Arecaceae, Araceae, Anacardiaceae, Burseraceae e Caryocaraceae. The bothanic species that presented a major cultural importance established by Use Value Estimate were Oenocarpus bacaba Mart., Astrocaryum aculeatum Mart., Heteropsis off. Spruceana Schott., Philodendron spruceanum (Schott & sine ref.) and Attalea attaleoides Mart. The data generated through this study points into the direction of viability to introduce a communitarian forest management project of multiple use on Road of Varzea, Silves AM area.
Keywords: Manejo dos recursos madeireiros; Manejo dos recursos não-madeireiros; Agricultura familiar; Manejo florestal comunitário